Accurate Potential Energy Function and Spectroscopic Properties of NS (X2Π) via Extrapolation to the Complete Basis Set Limit (Journal of Atomic and Molecular Sciences, 2017)
Potential energy curves (PECs) for the ground electronic state of NS are acquired by means of fitting the ab initio energies computed at the multi-reference configuration interaction method with the Davidson correction in combination with a series of correlation-consistent basis sets from Dunning: aug-cc-pVXZ (X = T, Q, 5 and 6). In order to obtain PECs with high accuracy, the PECs computed with aug-cc-pV(Q,5)Z basis sets are extrapolated to the complete basis set limit. Such PECs are then used to fit the analytical potential energy functions (APEFs) with the extended Hartree-Fock approximate correlation energy method. Based on the APEFs of NS(X²Π), reliable and accurate spectroscopic parameters are obtained. By solving the radial Schrödinger equation numerically, we can acquire the complete set of vibrational levels, inertial rotation constant, centrifugal distortion constants and classical turning points when J = 0. As a whole, our research data can be regarded as a reference for prospective research on the NS molecule.
Keywords: --